CONFIDENTIALITY IN FAMILY COUNSELLING: CHALLENGES AND EFFORTS TO DEAL WITH ADOLESCENT PROBLEMS - Annisa Fitria Suherman; Nandang Budiman; Nadia Aulia Nadhirah (Universitas Pendidikan Indonesia, 2023)
Confidentiality is an important aspect of the counselling process, particularly in family counselling, where counsellors must balance the needs and rights of individual family members with the family as a whole. This article explores the challenges and efforts in maintaining confidentiality in family counselling for adolescent problems. This research was conducted using a systematic literature review method. The researcher begins by outlining the legal and ethical considerations related to confidentiality and its exceptions, then discusses the challenges faced by family counsellors when confronted with adolescents and their families. The research also explores the different strategies counsellors use to maintain confidentiality while still addressing the needs of the family as a whole, including obtaining consent, setting clear boundaries, and building rapport with the adolescent and family. The article also discusses the importance of ongoing communication and cooperation with other professionals involved in the adolescent's care, such as school counsellors to authorities. Overall, this article highlights the complex nature of confidentiality in family counselling, especially when working with adolescents, and emphasises the importance of thoughtful and collaborative efforts to maintain privacy and still provide the best outcomes for the counsellor.